Safety and Efficacy of Alectinib in the First Line for ALK-Mutated Lung Cancer: A Real-World Data from India - Singh, Ajaykumar; Noronha, Vanita; Patil, Vijay; Menon, Nandini; Kapoor, Akhil; Trikha, Mehak; Manmode, Sima; Kaushal, Rajiv; Pai, Trupti; Purandare, Nilendu; Janu, Amit; Majumdar, Anuradha; Ubharay, Ahmad Ashfaq Ahmad; Prabhash, Kumar (South Asian Journal of Cancer, 2025)
Advanced/metastatic ALK-mutated lung cancer has excellent long-term survival due availability of multiple targeted drugs. Alectinib is one of the preferred first-line therapies based on the Alex trial data. We present a real-world outcome with alectinib in first-line setting in low- and middle-income country (LMIC) like India.We conducted a retrospective audit of ALK positive patients who received alectinib in first-line setting at the Medical Oncology Department, Tata Memorial Hospital, Mumbai, Maharashtra, India. We included patients who were started on alectinib between January 2018 and March 2022. The patients underwent routine blood and radiological evaluation every 2 to 3 months. We analyzed the data for progression-free survival (PFS), overall survival (OS), and safety profile.A total of 50 patients received alectinib in the specified period. The median age was 52.5 years (range: 28–81 years), 72% of the patients were 60 years or less; 54% of patients being male and 46% female. Eastern Cooperative Oncology Group-Performance Status (PS) 0 to 1 70%, PS 2 24%, and PS ¾ 6%. Methods for ALK testing were immunohistochemistry 92%, fluorescence in situ hybridization 2%, and next-generation sequencing 6%. The most common sites of metastasis before starting alectinib were bone (52%), pleura (42%), brain (30%), and lung (28%). Note that 66 and 33% patients received brain radiotherapy or bone-modifying agent for the central nervous system or bone metastasis, respectively. The median follow-up period was 18 months (13.1–22.8 months). Objective response rate was 76%, with partial response 74%, complete response 4%, and stable disease 16%. Median PFS and median OS were not reached, yet the expected 3-year PFS rate was 69.3% and 3-year OS rate was 85.7%, respectively. The most common sites of progression were the pleura and liver. Majority of side effects were grade 1 or 2 only with the most common being anemia, only one patient had grade 3 side effect (anemia). No drug interruption or dose modifications were needed in any patient.This real-world data from LMIC confirm the safety and efficacy of alectinib in the first-line setting matching that of registration studies with similar safety and tolerance, without any new alarm.
Keywords: alectinib; ALK; anaplastic lymphoma kinase; LMIC; low- and middle-income countries; OS; overall survival; PFS; progression-free survival